Eigenvalues of Non-Linear Problems Lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Varenna (Como), Italy, June 16-25, 1974 - Prodi, G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
H. Amann: Nonlinear eigenvalue problems in ordered Banach spaces.- P.C. Fife: Branching phenomena in fluid dynamics and chemical reaction-diffusion theory.- W. Klingenberg: The theory of closed geodesics.- P. Rabinowitz: Variational methods for nonlinear eigenvalue problems.- M. Reeken: Existence of solutions to the Hartree-Fock equations.- R. Turner: Positive solutions of nonlinear eigenvalue problems.
H. Amann: Nonlinear eigenvalue problems in ordered Banach spaces -- P.C. Fife: Branching phenomena in fluid dynamics and chemical reaction-diffusion theory -- W. Klingenberg: The theory of closed geodesics -- P. Rabinowitz: Variational methods for nonlinear eigenvalue problems -- M. Reeken: Existence of solutions to the Hartree-Fock equations -- R. Turner: Positive solutions of nonlinear eigenvalue problems.
Keywords: Partial differential equations; Fluid mechanics; Partial Differential Equations; Engineering Fluid Dynamics